Nanocarriers-Assisted Needle-Free Vaccine Delivery Through Oral and Intranasal Transmucosal Routes: A Novel Therapeutic Conduit - Mangla, Bharti; Javed, Shamama; Sultan, Muhammad H.; Ahsan, Waquar; Aggarwal, Geeta; Kohli, Kanchan (Frontiers in Pharmacology, 2022)
Drug delivery using oral route is the most popular, convenient, safest and least expensive approach. It includes oral transmucosal delivery of bioactive compounds as the mucosal cavity offers an intriguing approach for systemic drug distribution. Owing to the dense vascular architecture and high blood flow, oral mucosal layers are easily permeable and can be an ideal site for drug administration. Recently, the transmucosal route is being investigated for other therapeutic candidates such as vaccines for their efficient delivery. Vaccines have the potential to trigger immune reactions and can act as both prophylactic and therapeutic conduit to a variety of diseases. Administration of vaccines using transmucosal route offers multiple advantages, the most important one being the needle-free (non-invasive) delivery. Development of needle-free devices are the most recent and pioneering breakthrough in the delivery of drugs and vaccines, enabling patients to avoid needles, reducing anxiety, pain and fear as well as improving compliance. Oral, nasal and aerosol vaccination is a novel immunization approach that utilizes a nanocarrier to administer the vaccine. Nanocarriers improve the bioavailability and serve as adjuvants to elicit a stronger immune response, resulting in increased effectiveness of vaccination. Drugs and vaccines with lower penetration abilities can also be delivered transmucosally while maintaining their biological function. The development of micro/nanocarriers for transmucosal delivery of macromolecules, vaccines and other substances is currently drawing much attention and a number of studies were performed recently. This comprehensive review is aimed to summarize the most recent investigations on needle-free and non-invasive approaches for the delivery of vaccines using oral transmucosal route, their strengths and associated challenges. The oral transmucosal vaccine delivery by nanocarriers is the most upcoming advancement in efficient vaccine delivery and this review would help further research and trials in this field.